Perbedaan Pandangan Politik antara Al Azhar dan Ikhwan Al Muslimin dalam Merespon Kudeta Militer Tahun 2013 - Muhammad Anas; Yon Machmudi (Jurnal ICMES, 2019)
This articles discusses the political differences between Al Azhar and the Muslim Brotherhood (Ikhwan Al Muslimin) in a coup against President Mohammed Morsi on July 3, 2013. It is interesting that Al Azhar as one of the most influential religious institutions in the Islamic world in general and Egypt in particular, supporting the military coup led by General Abdul Fattah al-Sisi against Morsi, the first president of Egypt's who was democratically elected and also promoted by the largest Islamic movement in the 21st century, namely the Muslim Brotherhood. Previous studies have not been yet specifically discussed the differences between these two institutions in this coup. This study uses qualitative methods named causal explanation which seeks to explain the causes of the observed phenomena. The method of data analysis is content analysis of various documents related to the research topic. The data was collected by literature studies and interviews. This articles found that both Al Azhar and Ikhwan Al Muslimin have a significant different view on politics even though historically both also have close relationship in developing religious acitivities in Egypt. Al-Azhar Institution in this context loses its independence which encourages its involvement in conflicts between the state and Ikhwan Al Muslimin. In general, the political relationship between the two institutions is largely determined by the relationship between Ikhwan Al Muslimin and the ruling regime.